Flexible learning in an information society - Khan, Badrul H. (Badrul Huda) 1958-; Gale Group (Hershey, Penn. Information Science Pub., 2007)
This book uses a flexible learning framework to explain the best ways of creating a meaningful learning environment. This framework consists of eight factors - institutional, management, technological, pedagogical, ethical, interface design, resource support, and evaluation; a systematic understanding of these factors creates successful flexible learning environments.
Electronic reproduction.
Keywords: Distance education; Instructional systems -- Design; Educational technology; Effective teaching; Open learning; Effective teaching -- Evaluation; Electronic books